(untitled) (Cadernos de Sociomuseologia, 2025)
The present museological research sought to understand and question the museum based on the School of Thought of Sociomuseology, which outlines theoretical and applied activities that involve an attentive and active museological work on contemporary issues, based on a non- neutral posture. Certain Brazilian practices of Social Museology were also evoked, and thus fieldwork was carried out at the Historical Museum Frankfurt that aimed at incorporating these references and contributing to the institution’s range of methods and participatory formats, intended to approach the present time and include the plurality of perspectives in the search for endorsement from the society. Also drawing on the institution’s existing practices, various actions were carried out, and three main projects dealt with topics such as the city itself, gender issues, and migration. In this perspective, the use of cinema was proposed as a creative tool in the conception and execution of participatory musealization processes, in what was called ‘cinemuseological imagination’. In addition, reflexivity and statements from participants and colleagues were used to highlight aspects about participation at the museum, how the projects undertaken complemented their actions, and the impact on the empowerment of the people involved according to their perceptions. Keywords: Sociomuseology; Empowerment; Participation; Cinema; Historical Museum Frankfurt .